Study of Environmental Parameters on Lobster (Panulirus spp.) Enlargement with Fixed Cage at GWD, Banyuwangi - Putra, Riswanda Rangga; Nugraha, Dimas Putra Wahyu; Albarkah, M. Rafly; Ma’arif, M. Chusnan; Fatih, M. Fachrul; Hadi, Moch. Irfan; Violando, Wiga Alif; Nusa, Raras Widya (Biota, 2022)
One of the marine commodities, Lobster (Panulirus spp.), has unabated demand in the global market, while, Lobster production remains static due to the difficulty of implementing its rearing activities. Relative rearing of lobster (Panulirus spp.) is usually performed using the floating net cage method with calm water conditions. In contrast, areas with extreme weather conditions tend to have difficulty applying this method. The potential of using the fixed cage method was assessed by rearing the Lobster at Pesona Bahari Banyuwangi Fish Cultivation Group. This research aimed to investigate the feasibility of the environmental conditions in the waters of GWD, Banyuwangi. The study was conducted for three months. Data such as temperature and light intensity through the help of a pendant was collected. Water quality parameters were recorded during this study, including salinity, pH, dissolved oxygen, and current velocity. Sampling was conducted four times to see the relationship between length and weight. The results showed that the GWD environmental parameters were very supportive for lobster rearing, with temperature values ​​ranging from 27.2oC - 30.1oC, DO around 4.6 mg/l - 5.2 mg/l, salinity 28o/oo - 30o/oo, pH 7 - 8.2, the current speed is 0.468 m/s, and the light intensity is 0 lux - 3,616 lux. The growth pattern of all sampling results except sampling 2 (isometric) has a negative allometric result, with length and weight having a solid relationship. The fixed cage method is considered suitable for lobster rearing activities because the environmental parameters follow their natural habitat and the Fulton condition factor (K) value of more than 1. The greater the value of the Fulton condition factor (K), the healthier the condition lobster.